Geographic variation in malignant cardiac tumors and their outcomes: SEER database analysis - Rahouma, Mohamed; Khairallah, Sherif; Dabsha, Anas; Baudo, Massimo; El-Sayed Ahmed, Magdy M.; Gambardella, Ivancarmine; Lau, Christopher; Esmail, Yomna M.; Mohamed, Abdelrahman; Girardi, Leonard; Gaudino, Mario; Lorusso, Roberto; et al. (Frontiers in Oncology, 2023)
Introduction: Primary malignant cardiac tumors (PMCTs) are rare. Geographical distribution has been demonstrated to affect cancer outcomes, making the reduction of geographical inequalities a major priority for cancer control agencies. Geographic survival disparities have not been reported previously for PMCT and the aim of this study is to compare the prevalence and the long-term survival rate with respect to the geographic location of PMCTs using the Surveillance, Epidemiology, and End Results (SEER) research plus data 17 registries between 2000 and 2019. Methods: The SEER database was queried to identify geographic variation among PMCTs. We classified the included states into 4 geographical regions (Midwest, Northeast, South and West regions) based on the U.S. Census Bureau-designated regions and divisions. Different demographic and clinical variables were analyzed and compared between the four groups. Kaplan Meier curves and Cox regression were used for survival assessment. Results: A total of 563 patients were included in our analysis. The median age was 53 years (inter-quartile range (IQR): 38 - 68 years) and included 26, 90, 101, and 346 patients from the Midwest, Northeast, South, and West regions respectively. Sarcoma represented 65.6% of the cases, followed by hematological tumors (26.2%), while mesothelioma accounted for 2.1%. Treatment analysis showed no significant differences between different regions. Median overall survival was 11, 21, 13, and 11 months for Midwest, Northeast, South and West regions respectively and 5-year overall survival was 22.2%, 25.4%, 14.9%, and 17.6% respectively. On multivariate Cox regression, significant independent predictors of late overall mortality among the entire cohort included age (Hazard Ratio [HR] 1.028), year of diagnosis (HR 0.967), sarcoma (HR 3.36), surgery (HR 0.63) and chemotherapy (HR 0.56). Conclusion: Primary malignant cardiac tumors are rare and associated with poor prognosis. Sarcoma is the most common pathological type. Younger age, recent era diagnosis, surgical resection, and chemotherapy were the independent predictors of better survival. While univariate analysis revealed that patients in the South areas had a worse survival trend compared to other areas, geographic disparity in survival was nullified in multivariate analysis.